2020
DOI: 10.1136/openhrt-2020-001430
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review and meta-analysis of prolactin and iron deficiency in peripartum cardiomyopathy

Abstract: ObjectivesWe conducted a systematic review and meta-analysis of studies that compared levels of molecular biomarkers in women with peripartum cardiomyopathy (PPCM) to those in healthy pregnant and postpartum women to: (1) assess the evidence for prolactin (PRL) metabolism in PPCM, (2) ascertain the evidence for biomarkers of iron deficiency in PPCM, (3) identify other biomarkers associated with PPCM.MethodsWe searched Medline, Embase, Cumulated Index to Nursing and Allied Health Literature (CINAHL) and the Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…In a study conducted by Dhesi S [9] & Lindley KJ [10] and their colleagues confirms underlying mechanism and the findings of our study. While some of the international studies had also observed non-traditional risk factors of CHF in patients with PPCM like increased levels of uric acid, mother of male infant, and higher levels of prolactin [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Dhesi S [9] & Lindley KJ [10] and their colleagues confirms underlying mechanism and the findings of our study. While some of the international studies had also observed non-traditional risk factors of CHF in patients with PPCM like increased levels of uric acid, mother of male infant, and higher levels of prolactin [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in variable concentrations, prolactin can regulate the contraction and relaxation of vascular smooth muscle, thus modulating vascular tone. In animal models, excess oxidative stress is postulated to mediate the upregulation of prolactin cleavage factors, leading to an increase in the concentration of a prolactin isoform with anti‐angiogenic and apoptotic properties 28,29 . This isoform has been associated with dysfunctional cardiometabolism, destruction of the cardiac microvasculature and impaired cardiac muscle contraction 30,31 .…”
Section: Unpredictable Cs In Pregnancy: De Novomentioning
confidence: 99%
“…Several studies have determined whether specific biomarkers were associated with PPCM, which were summarized by Cherubin et al 95 . The authors evaluated 117 biomarkers from 31 case-control studies.…”
Section: Biomarkersmentioning
confidence: 99%
“…See Table 1 for an overview of biomarkers. A quantitative meta-analysis suggested that patients with PPCM had higher levels of natriuretic peptides, troponin, CRP, and white blood cell counts, but reduced levels of albumin and selenium compared with healthy controls 95 . Note that these biomarkers mostly reflect the presence of cardiomyopathy and appear to be unspecific for PPCM.…”
Section: Biomarkersmentioning
confidence: 99%